2000
DOI: 10.1515/cclm.2000.127
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein and Bioavailability-Implication of Polymorphism

Abstract: P-Glycoprotein (P-gp) may have a significant impact on systemic and tissue/cellular bioavailability of drugs because it functions as an "anti-absorption" mechanism that effluxes drug molecules out of the lipid bilayer and cytoplasm. The ability to reduce bioavailability at the tissue/cellular level was first discovered during the investigation of the causes of multidrug resistance (MDR) in cancer chemotherapy. Initially, it was thought that MDR is only caused by P-gp. Recently, many other transporters such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Additionally, some of the efflux transporters (e.g. p-glycoprotein) may be capable of sequestering metabolites in the cytosolic domain and then pump them out once the complex merged into the cell membrane [9]. Moreover, we have shown that multiple transporters are involved in the cellular excretion of phase II conjugates, creating a network that is far more complex than that depicted in Fig.…”
Section: Complexity In Sorting Out the Coupling Processesmentioning
confidence: 86%
See 1 more Smart Citation
“…Additionally, some of the efflux transporters (e.g. p-glycoprotein) may be capable of sequestering metabolites in the cytosolic domain and then pump them out once the complex merged into the cell membrane [9]. Moreover, we have shown that multiple transporters are involved in the cellular excretion of phase II conjugates, creating a network that is far more complex than that depicted in Fig.…”
Section: Complexity In Sorting Out the Coupling Processesmentioning
confidence: 86%
“…Substrates of P-gp have diverse chemical structures, but the vast majority is lipophilic planar molecules. Most P-gp substrates are uncharged, but a few weakly basic or acidic compounds such as methotrexate are also transported [9].…”
Section: Mdr1 or P-glycoprotein (P-gp)mentioning
confidence: 99%
“…As has been shown by us in the previous review [90] parent compound itself may also be subjected to efflux at the apical side or basolateral side or both [101]. Moreover, some of the efflux transporters, e.g., p-glycoprotein, may be capable of sequestering metabolites in the cytosolic domain and then pump them out once the complex merged into the cell membrane [102]. Lastly, we and other investigators have found that multiple transporters, e.g., MRP2, OAT, are involved in the cellular excretion of phase II conjugates of natural polyphenols [51,99,103,104].…”
Section: Coupling Of Efflux Transporters and Conjugation Enzymes [90]mentioning
confidence: 87%
“…Several recent reports indicate that polymorphisms are relatively common in the human MDR1 gene (Yoshimoto et al, 1988;Mickley et al, 1998;Decleves et al, 2000;Hoffmeyer et al, 2000;Liu and Hu 2000;Ameyaw et al, 2001;Brinkmann et al, 2001;Cascorbi et al, 2001;Hitzl et al, 2001;Ito et al, 2001;Kerb et al, 2001;Kim et al, 2001;Schaeffeler et al, 2001). This finding has stimulated interest in whether common coding polymorphisms affect function of P-gp and/or whether polymorphic variants are linked to altered drug pharmacokinetics.…”
mentioning
confidence: 99%